Pengaruh Komitmen Organisasi terhadap Kinerja Organisasi Bank Syariah: Peran Turnover Intention sebagai Variabel Intervening - Nurwahidah Nurwahidah; Muhammad Jamil (Universitas Batanghari Jambi, 2020)
This study aims to analyze the effect of organizational commitment on the organizational performance of Bank Aceh Syariah by involving turnover intention as an intervening variable. The research sample consisted of 206 employees of the bank's operational head office. Data collection using a questionnaire and then the structural equation model is applied to analyze the functional relationship between variables. The study found that organizational commitment has a positive and significant effect on organizational performance, and a negative and significant impact on turnover intention. Furthermore, turnover intention has a negative and significant effect on organizational performance. The existence of turnover intention as an intervening variable exacerbates the effect of organizational commitment on the bank's organizational performance.